School of Social Work 1991 - Dr. Jose Villa, "Understanding the Power Structure" - Castellano, Alcario:::creator:::::::::::: (2024)
Video and transcripts of an event called, "Understanding the Power Structure" with the faculty members of the School of Social Work, including Dr. Jose Villa.